Gallbladder Paraganglioma- A Rare Case Report - Doly, Halima Khatun; Shakila Jannat; Sayeed Bin Sharif; Syeda Noorjahan Karim; Md Atiqur Rahman; ASM Akramul Islam (KYAMC Journal, 2023)
A 34-years-old married middle-class housewife without diabetes, hypertension or betel-nut- chewing hailing from Manikganj, Dhaka; came with the outside diagnosis as neuroendocrine tumor of the gallbladder to the Oncology Department of Khwaja Yunus Ali Medical College and Hospital (KYAMCH). She was admitted in the hospital with complaints of upper abdominal pain, abdominal bloating, weakness, anorexia, nausea and heartburn while taking fatty food. According to her Ultrasonography (USG) of the abdomen, a soft tissue mass was found in the gallbladder with unremarkable routine blood examination including tumor markers. She underwent open cholecystectomy with the suspicion of cancer. Grossly, gallbladder was measures 7.0x 5.0 cm with 0.3 cm wall thickness and on opening a polypoid nodule is found. Before treatment on request from the Oncology Department of KYAMCH, all slides were reviewed and a histopathological diagnosis of paraganglioma was made on the basis of organoid, nested or lobules (Zellballen pattern) of tumor cells in the lamina propria surrounded by a prominent fibrovascular stroma. Atypical mitoses, tumor necrosis, lymphovascular or perineural invasion was not found. The IHC reveals diffuse and strong positive reactions to NSE and CD56 for chief cells and strong positive reaction to S-100 protein for sustentacular cells. The epithelial tumor was ruled out by CK negative reaction. Therefore, the diagnosis of paraganglioma of the gallbladder was established. Because of the positive reaction to sustentacular cells, the neuroendocrine tumor has been excluded. To our knowledge, this type of case has not been reported in our country. On clinical follow-up the patient was found healthy. KYAMC Journal Vol. 14, No. 01, April 2023: 57-61